CXCL9 and CXCL10 are differentially associated with systemic organ involvement and pulmonary disease severity in sarcoidosis. (January 2020) - Arger, Nicholas K.; Ho, Melissa E.; Allen, Isabel E.; Benn, Bryan S.; Woodruff, Prescott G.; Koth, Laura L.
Abstract: Background: Sarcoidosis is a granulomatous inflammatory disease with limited blood markers to predict outcomes. The interferon-gamma (IFN-γ)-inducible chemotactic cytokines (chemokines), CXCL9 and CXCL10, are both increased in sarcoidosis patients, yet they possess important molecular differences. Our study determined if serum chemokines correlated with different aspects of disease severity. Methods: We measured CXCL9 and CXCL10 serum levels at initial study visits and longitudinally in sarcoidosis subjects using ELISA. We examined these chemokines' relationships with pulmonary and organ involvement outcomes, their gene expression, peripheral blood immune cell populations, and immunosuppression use. Results: Higher CXCL10 levels negatively correlated with FVC, TLC, and DLCO at subjects' initial visit and when measured repeatedly over two years. CXCL10 also positively correlated with longitudinal respiratory symptom severity. Additionally, for every log10 (CXCL10) increase, the risk of longitudinal pulmonary function decline increased 8.8 times over the 5-year study period (95% CI 1.6–50, p = 0.014, log10 (CXCL0) range 0.84–2.7). In contrast, CXCL9 levels positively correlated with systemic organ involvement at initial study visit (1.5 additional organs involved for every log10 (CXCL9) increase, 95% CI 1.1–2.0, p = 0.022, log10 (CXCL9) range 1.3–3.3). CXCL10, not CXCL9, positively correlated with its own blood gene expression and monocyte level. Immunosuppressive treatment was associated with lower levels of both chemokines. Conclusions: In sarcoidosis subjects, serum CXCL9 levels correlated with systemic organ involvement and CXCL10 levels strongly correlated with respiratory outcomes, which may ultimately prove helpful in clinical management. These differing associations may be due to differences in cellular regulation and tissue origin. Highlights: Serum CXCL10 was negatively associated with FVC, DLCO, and TLC in sarcoidosis subjects. Subjects with increased levels of CXCL10 had increased risk of PFT declines. Serum CXCL9 positively correlated with organ involvement. CXCL10 gene expression and blood monocyte levels positively correlated with CXCL10 protein levels, whereas CXCL9 did not. Both CXCL9 and CXCL10 were lower with higher immunosuppression usage.